Age‐ and sex‐specific pediatric reference intervals for neutrophil‐to‐lymphocyte ratio, lymphocyte‐to‐monocyte ratio, and platelet‐to‐lymphocyte ratio. (23rd November 2021) - Moosmann, Julia; Krusemark, Anja; Dittrich, Sven; Ammer, Tatjana; Rauh, Manfred; Woelfle, Joachim; Metzler, Markus; Zierk, Jakob
Abstract: Introduction: Neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and lymphocyte‐to‐monocyte ratio (LMR) are emerging biomarkers for systemic inflammation and have been shown to predict morbidity and mortality for several diseases. However, lack of pediatric reference intervals (RIs) prevents their comprehensive use in patient care and medical research. Material and Methods: We calculated reference intervals and corresponding confidence intervals for NLR, PLR, and LMR from birth to 18 years using a data‐mining approach: We analyzed 232 746 blood counts from 60 685 patients performed during patient care and excluded patients with elevated C‐reactive protein and procalcitonin. Test results were separated according to age and sex, and the distribution of physiological ratios was estimated using an indirect approach ( refineR ). Additionally, we investigated the ratios' diagnostic benefit for different inflammatory diseases (acute appendicitis, asthma, Bell's palsy, Henoch‐Schonlein purpura, and cystic fibrosis) using the newly obtained reference intervals. Results: We estimated age‐ and sex‐specific reference intervals from birth to adulthood for NLR, PLR, and LMR. Analyses in pediatric inflammatory diseases showed that PLR and LMR were poor markers to detect the examined inflammatory diseases, while NLR was significantly increased in patients with appendicitis and asthma. Conclusion: We provide pediatric reference intervals for NLR, PLR, and LMR to improve the interpretation of these biomarkers in children.